Effects of topical budesonide on epithelial restitution in vivo in guinea pig trachea. Issue 7 (July 1995) - Erjefält, J S; Erjefält, I; Sundler, F; Persson, C G
Abstract : BACKGROUND--Continuous epithelial shedding and restitution processes may characterise the airways in diseases such as asthma. Epithelial restitution involves several humoral and cellular mechanisms that may potentially be affected by inhaled anti-asthma drugs. The present study examines the effect of a topical steroid on epithelial restitution in vivo in the guinea pig. METHODS--The airway epithelium was mechanically removed from well defined areas of guinea pig trachea without surgery and without damage to the basement membrane or bleeding. An anti-inflammatory dose of budesonide (1 mg) was administered repeatedly to the tracheal surface by local superfusion 24 hours before, at (0 hours), and 24 hours after the denudation. Migration of epithelial cells, formation of a plasma exudation-derived gel, and appearance of luminal leucocytes were recorded by scanning electron microscopy. Cell proliferation was visualised by bromodeoxyuridine immunohistochemistry and tissue neutrophils and eosinophils by enzyme histochemistry. RESULTS--Immediately after creation of the denuded zone ciliated and secretory cells on its border dedifferentiated, flattened out, and migrated speedily (mean (SE) 2.3 (0.3) micron/min) over the basement membrane. After 48 hours the entire denuded zone (800 microns wide) was covered by a tightly sealed epithelium; at this time increased proliferation was observed in new and old epithelium and subepithelial cells. Budesonide had no detectable effect on epithelial dedifferentiation, migration, sealing, or proliferation. Immediately after denudation and continuously during the migration phase plasma was extravasated creating a fibrinous gel rich in leucocytes, particularly neutrophils, over the denuded area. Budesonide had no effect on either the gel or the leucocyte density. CONCLUSIONS--These observations suggest that topical glucocorticoids may not interfere with a fast and efficient restitution of the epithelium in the airways.